2004
DOI: 10.1128/iai.72.7.4279-4281.2004
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility of Secretor Factor Gene Fut2 -Null Mice to Experimental Vaginal Candidiasis

Abstract: Fut2-LacZ-null mice, which are a model of the human ABO and Lewis nonsecretor group, display increased susceptibility to experimental yeast vaginitis, indicating a role for ␣(1,2)fucosylated cervical glycans in mucosal defense. However, the lack of significant effect of competitive inhibition by exogenous neoglycoproteins in this study emphasizes the complexity of Candida-epithelial cell adhesion events.Recurrent vulvovaginal candidiasis (RVVC) is a mucosal infection caused by the opportunistic fungus Candida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…In particular, the association between infections and BGA polymorphisms has been extensively investigated, although conclusive results have been obtained in a minority of cases. For example, specific BGA alleles have been shown to alter susceptibility to malaria (Moulds and Moulds 2000), while FUT2 variants (Lewis system) influence the predisposition to Norwalk virus (Lindesmith et al 2003) and Campylobacter (Ruiz-Palacios et al 2003) infection, as well as to vulvovaginal candidisis (Hurd and Domino 2004) and urinary tract infections (Schaeffer et al 2001).…”
mentioning
confidence: 99%
“…In particular, the association between infections and BGA polymorphisms has been extensively investigated, although conclusive results have been obtained in a minority of cases. For example, specific BGA alleles have been shown to alter susceptibility to malaria (Moulds and Moulds 2000), while FUT2 variants (Lewis system) influence the predisposition to Norwalk virus (Lindesmith et al 2003) and Campylobacter (Ruiz-Palacios et al 2003) infection, as well as to vulvovaginal candidisis (Hurd and Domino 2004) and urinary tract infections (Schaeffer et al 2001).…”
mentioning
confidence: 99%
“…In our animal model of nonsecretors, Fut2-null mice, we reported an increased susceptibility to experimental vaginitis 16. Fut2 is expressed in secretory cells of uterine and endocervical glandular epithelium, but expression was not detected at the major site of Candidal adhesion and invasion, i.e.…”
Section: Introductionmentioning
confidence: 85%
“…The authors suggest that the H disaccharide-containing cell surface glycoconjugates may act as host receptors for Candida albicans on the buccal mucosa as a part of a complex adhesion mechanism probably requiring multireceptor specificities given that total adhesion inhibitions were never obtained throughout the study. Other studies have shown that ABH non-secretors have a higher incidence of candidiasis (BurfordMason, Weber & Willoughby, 1988; Hurd & Domino, 2004;Lamey et al, 1991), suggesting that fucosylated oligosaccharides may be suitable as functional food ingredients for individuals who have a high susceptability to oral candidiasis. The potential of milk oligosaccharides in preventing adherence of other fungal species remains unknown.…”
Section: Fungal Anti-adhesionmentioning
confidence: 96%